1989
DOI: 10.1128/mcb.9.6.2574
|View full text |Cite
|
Sign up to set email alerts
|

E1a transactivation of the human HSP70 promoter is mediated through the basal transcriptional complex.

Abstract: We have examined the promoter sequence requirements for Ela transactivation of the human HSP70 gene by using a transient cotransfection assay. A 5' deletion study has defined a basal transcription unit extending to -74 relative to the transcription initiation site which was fully Ela responsive. Further deletion, abolishing a CCAAT element at -67, drastically reduced basal and Ela-induced expression. A linker-scanner analysis has identified four functional elements within the basal transcription unit which may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(121 citation statements)
references
References 50 publications
6
114
1
Order By: Relevance
“…In contrast, peptides such as nerve growth factor and brain-derived neurotrophic factor (68,69), N-methyl-D-aspartate, or the excitatory ␥-aminobutyric acid neurotransmitters (69) trans-activate CREB by phosphorylation via the calcium/calmodulin-dependent kinase IV and a mitogen-activated protein kinase (68,69). Phosphorylation of CREB leads to induction of downstream early genes such as c-fos (70), zif/268 (71), hsp70 (72), and bcl-2 (73) that may either increase biosynthesis of neurotrophic factors or block cell death pathways (69,73). c-Fos induces biosynthesis of neurotrophic factors by increasing activator protein-1 (AP-1) binding activity (75).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, peptides such as nerve growth factor and brain-derived neurotrophic factor (68,69), N-methyl-D-aspartate, or the excitatory ␥-aminobutyric acid neurotransmitters (69) trans-activate CREB by phosphorylation via the calcium/calmodulin-dependent kinase IV and a mitogen-activated protein kinase (68,69). Phosphorylation of CREB leads to induction of downstream early genes such as c-fos (70), zif/268 (71), hsp70 (72), and bcl-2 (73) that may either increase biosynthesis of neurotrophic factors or block cell death pathways (69,73). c-Fos induces biosynthesis of neurotrophic factors by increasing activator protein-1 (AP-1) binding activity (75).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, E1A binding to Rb family members through the CR2 region leads to the release of bound E2F transcription factors that repress tran- scription (54). By binding the heat shock protein/CCAAT-binding protein HSP-CBP through the CR3 region (55), E1A also stimulates transcription of the heat shock protein HSP70 (56,57). HSP-CBP was originally identified as a transcription factor that binds to the CCAAT box in the HSP70 promoter (58).…”
Section: Discussionmentioning
confidence: 99%
“…For example, adenovirus EIA was shown to increase expression of the hsp70 gene by stimulating the promoter activity [22]. The mechanism of EIA·activation has been studied by analyzing the hsp70 promoter [24][25][26][27]. It has been shown that both the TATA' and the 'CAAT' elements in the hsp70 promoter are targets of EIA·activation [25][26][27].…”
Section: Discussionmentioning
confidence: 99%